Notes on the genus Phanoperla Banks from Sri Lanka and India (Plecoptera: Perlidae) - Mason, Denise (Illiesia, 2015)
Eggs of Phanoperla nana Zwick 1982a, P. wedda Zwick 1982a, and an unassociated female from Sri Lanka are described based on scanning electron micrographs. The putative female and egg are described for P. peniculus Kawai 1975, and a revised key is provided for Indian and Sri Lankan Phanoperla males.
Keywords: entomology; stoneflies; Plecoptera; Perlodidae; Phanoperla; egg morphology; new records; India